Effect of Fluorine Patterns on Electronic Transport in Fluorinated Graphene. Issue 4 (18th February 2020) - Yamaletdinov, Ruslan D.; Katkov, Vsevolod L.; Nikiforov, Yaroslav A.; Okotrub, Alexander V.; Osipov, Vladimir A.
Abstract: Within the framework of stochastic reactive molecular dynamics simulations a statistical method for generating fluorinated graphene structures with desirable fluorine distribution is developed. Electronic transport properties of fluorinated graphene in a wide range of functionalization degrees and system ordering are investigated. A strong correlation between irregularities in fluorine distribution and electronic properties is found. In particular, proposed consideration allows for the reproduction of both the experimentally observed electron–hole asymmetry in transport properties of fluorinated graphene and a recently revealed conductivity peak at 10% fluoride content. Abstract : A new method for generation of fluorinated graphene structures with desirable fluorine distribution is presented. Electronic transport properties of fluorinated graphene in a wide range of functionalization degrees and system ordering are investigated. Irregularities in fluorine distribution lead to electron–hole asymmetry and formation of superstructures in electron density, which can explain an experimentally observed conductivity peak at 10% fluoride content.